Improving the Quality of Boiler Feed Water Based on the PDCA Cycle by Integrating Seven Tools - Ali Albana; Said Salim Dahda (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
A boiler is an equipment that produces steam, which is used as a heater, drives a turbine to produces electricity, and so on. In order to avoid reducing efficiency boilers and save operational costs due to the formation of scale and corrosion on pipes, special treatment is required for boiler water. However, the facts in the field are that many BFW (Boiler Feed Water) products are found that do not meet the quality requirements set by the company. PT. Petrokimia Gresik is an industrial chemical company that uses boilers to assist its production process. The method used in this study is quality control analysis with the PDCA approach and Seven Tools in the form of check sheets, histograms, Pareto diagrams, control charts, fishbone diagrams, and FMEA to identify the factors causing the occurrence of defective products and see the corrective actions that must be taken based on the factors causing the occurrence of defective products. Preventive maintenance was carried out to create and schedule socialization of SOPs, collect data on spare part replacements, and check the chemical content in work unit wastewater. Based on the research results, it reveals that the PDCA approach and Seven Tools can minimize defects and succeed in reducing SO3 and PO4 parameter defects by 67,5%. The proposed improvement efforts include preventive maintenance, monitoring the consistency of SOP implementation, identifying replacement spare parts, as well as checking chemical content in work unit wastewater.